Dystocia due to hydrocephalus calf in a buffalo cow - KUMARESAN, A; GARG, ABHISHEK; MAHAPATRA, U S; SHANKER, UMA; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2003)
A case of dystocia due to hydrocephalus calf in a buffalocow has been presented. Dystocia wasrelieved by incising the soft portiem of the hydrocephalus head thereby recuding foetus size.
Keywords: Buffalo; Dystocia; Hydrocephalus